If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 10 = -23 Reorder the terms: 10 + 3y = -23 Solving 10 + 3y = -23 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3y = -23 + -10 Combine like terms: 10 + -10 = 0 0 + 3y = -23 + -10 3y = -23 + -10 Combine like terms: -23 + -10 = -33 3y = -33 Divide each side by '3'. y = -11 Simplifying y = -11
| 4x+3x+5+2=56 | | x^2-24x-25=0 | | 7+4k-6= | | 25=3(x-7)+5 | | 8(1+r)=1+8r | | 8n(6n+7)=5 | | 4r+3r= | | 13x^2-8x=0 | | (y-7)-(y+4)=8y | | 3x^2-75=0 | | 5(x-2)=7x | | 3(x+3)+5=25 | | 18.03=3g+3.72 | | 9b+7-1= | | 10x-16=74 | | 1.32g-8=0.58 | | 6(5+7z)= | | 9x+8=71 | | 42=8m-13m | | 2(-x-1)=2x-34 | | 3(x-1)+5=25 | | 5(-7z-6)= | | 49x^2-196=0 | | 5t-0=-3t+7 | | 3(-14+2)=4(5-14) | | -5(n+8)=-98 | | 4g+3g+9g= | | x^2-13x=-30 | | 4(3x-2)=52 | | 5x^2-24x+18=0 | | 3x^2-6x+45=0 | | x^2-13=-30 |